Deciding for others reduces loss aversion - Ola Andersson; Håkan J. Holm; Jean-Robert Tyran; Erik Wengström (Research Institute of Industrial Economics (IFN), 2013)
We study risk taking on behalf of others, both with and without potential losses. A large-scale incentivized experiment is conducted with subjects randomly drawn from the Danish population. On average, decision makers take the same risks for other people as for themselves when losses are excluded. In contrast, when losses are possible, decisions on behalf of others are more risky. Using structural estimation, we show that this increase in risk stems from a decrease in loss aversion when others are affected by their choices.
Keywords: C91; D03; D81; G02; 330; Risk taking; loss aversion; experiment